078 High dose adenosine stress perfusion cardiovascular magnetic resonance imaging for detection of coronary artery disease. (22nd September 2015) - Weerackody, RP; Burchell, T; Mohiddin, S; Crake, T; Mathur, A; Westwood, MA; Davies, LC
Abstract : Introduction: CMR perfusion (CMRP) imaging using adenosine is increasingly used for the assessment of patients with known or suspected coronary artery disease. At a standard dose adenosine is well tolerated with a good safety profile but on occasion fails to produce a significant haemodynamic response. This may potentially lead to the misdiagnosis of significant ischaemia. We therefore examined whether using a higher dose in the these patients to induce a haemodynamic response would lead to the identification of additional perfusion defects. Methods: We prospectively recruited from 1230 consecutive patients undergoing CMRP. First pass CMRP was performed on a Philips Achieva CV 1.5T MR scanner (Philips, The Netherlands), with standardised acquisition protocol with standard dose adenosine (SDA) at 140 μg/kg/min for 3 min. Three short axis slices of 10 mm thickness were acquired per cardiac cycle using a single shot prospectively gated balanced TFE sequence (TR 2.5 ms, TE 1.3 ms, Flip angle 500 and voxel size 2.8×2.8 mm 2 ) after the administration of a 0.1 mmol/kg bolus of intravenous Gadolinium. Heart rate (HR) and blood pressure (BP) were recorded at baseline and during stress. Non responders were defined as those patients with a normal CMRP scan and blunted hamodynamic response (maximum HR increase <10 beats per minute and fall in systolic BP (SBP) <10 mmHg). CMRP in this group was then repeated with high dose adenosine (HDA) at 175 μg/kg/min for 3 min. CMRP images were interpreted by two independent experienced observers. Coronary angiographic data were analysed by an experienced interventionist who was blinded to the perfusion data. Results obtained at SDA and HDA (expressed as mean value value±SD) were compared using the student t test. Results: Fifty-one patients (4.1%) recieved HDA. HDA was well tolerated with no serious adverse events. Coronary angiographic data were available for 20 patients (39%). HDA stress resulted in a significant increase in HR and RPP in non responders (Abstract 78 Table 2 ). CMRP with HDA identified perfusion defects in 12 patients (24%) which were not present following stress with SDA. In 11 patients (92%) the identified perfusion defects correlated with significant stenosis (>70%) on the angiogram. Conclusion: HDA achieved significant heamodynamic end-points with no significant clinical adverse events. Additional perfusion defects in the non responders with SDA were found using HDA. The perfusion defects correlated with significant coronary stenoses. The use of HDA may be important in certain patients where there is little or no haemdynamic response to SDA.